2010
DOI: 10.3171/2010.1.peds09481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of integrating positron emission tomography during surgery in 85 children with brain tumors

Abstract: Object In this paper, the authors' goal was to evaluate the impact of PET information on brain tumor surgery in children. Methods Between 1995 and 2007, 442 children were referred to the authors' institution for a newly diagnosed brain lesion. Of these, 85 were studied with FDG-PET and/or L-(methyl-11C)-methionine –PET in cases in which MR images were unable to assist in selecting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 34 publications
2
56
2
3
Order By: Relevance
“…The latter was explained by false-negative scan findings. Another study in 85 pediatric patients revealed a significant impact of 18 F-FDG or 11 C-methionine PET on surgical decisions in all patients (39). Our study differs from these reports in that it was prospective, used 18 F-DOPA as a probe of amino acid transport, and determined whether intended management changes were in fact implemented.…”
Section: Discussioncontrasting
confidence: 48%
“…The latter was explained by false-negative scan findings. Another study in 85 pediatric patients revealed a significant impact of 18 F-FDG or 11 C-methionine PET on surgical decisions in all patients (39). Our study differs from these reports in that it was prospective, used 18 F-DOPA as a probe of amino acid transport, and determined whether intended management changes were in fact implemented.…”
Section: Discussioncontrasting
confidence: 48%
“…Prior research demonstrates that 18 F-FDG and 11 C-MET improve the quality of therapeutic management of pediatric brain tumors at the diagnostic, surgical, and postoperative level, particularly in ill-defined infiltrative tumors. 18 F-FDG presents some limitations in defining targets for biopsy in low-grade pediatric tumors, whereas 11 C-MET appears also to be a better tracer than 18 F-FDG for delineating tumor boundaries and for residual tumor detection (25,26). Other studies found a correlation between 18 F-FDG uptake and tumor malignancy; however, there was significant overlap between different grades of malignancy (27,28).…”
Section: Discussionmentioning
confidence: 93%
“…However, studies have demonstrated a high sensitivity and specificity of 90% for 11 C-methionine PET to detect tumor tissue and a better ability to detect tumor tissue than other diagnostic means such as CT or MRI (12). Additionally, in a recent study on gliomas in children, postoperative 11 C-methionine PET presented as neither falsepositive nor false-negative and was significantly better than MRI (P , 0.05) (41).…”
Section: Discussionmentioning
confidence: 95%